New streetwise; Upper intermediate ( Teacher's book ) - Rob Nolasco (Oxford Univ. Press, 2000)
This book contains an introduce to the course, detailed unit-by-unit teaching notes, plus answers to exercises, tapescripts, extra options, and background information; answers to Workbook exercises, six progress tests with answer key.